Community medicine in Nepal: opportunities and challenges - Rajbhandari, Renu; Gurung, Saraj; Gurung, Bhabisara (1999)
Renu Rajbhandari, Bhabisara Gurung and Saraj Gurung argue that globalization, open market economy, privatization of health institutions and natural resources, as well as paternalistic approaches and structures, have increasingly marginalized women in Nepal, particularly in rural areas. Indigenous knowledge, technology, experience and plant resources of medicinal values have been eroded. They show how the NGO WOREC has been working towards sustainable health facilities at the community level through 11 village development committees in three districts as an example of community based alternatives for sustainable healthy womanhood. - Reproduced
Keywords: Women - Nepal; Health services